DEVELOPING ADOBE FLASH CS 6 MEDIA OF INDEPENDENT REHABILITATION THERAPY PROGRAM FOR ANKLE INJURIES - Harun .; Fatimah - (Pelita - Jurnal Penelitian Mahasiswa UNY, 2013)
This study aimed to determine the design and develop Adobe Flash CS 6 audiovisualmedia of independent rehabilitation therapy for ankle injuries.The method used was Research Development (R D). The steps in developingthe audio-visual media of rehabilitation therapy for ankle injuries are as follows:(1) conducting needs analysis, (2) designing the model, (3) implementing, and(4) testing. The data were collected by measuring the functions in accordance with thedesigned media and using questionnaires to assess the feasibility of the media. Thedata were analyzed qualitatively.The result was the product of audio-visual media of rehabilitation therapy forankle injuries. The result of alpha testing showed that the media needed revisions. Theresult of the beta testing showed that the users could use the media well and wereinterested in the audio-visual media of rehabilitation therapy for ankle injuries.